ON APPROXIMATION OF SUM OF CONVERGENT SERIES - Daya Ram Paudyal; Lakshmi Narayan Mishra (The Journal of Engineering and Exact Sciences)
The paper has given a clear opinion on the progress of environmental protection and sustainability in the Nigerian context. The environmental regulations scenario in the country is marred by malpractices and corruption more stringent policy enforcement will help in the achievement of environmental protection.  This paper deals with a specialized method of approximating the sum of an infinite series containing positive terms which are monotonically decreasing. The analysis has been done by taking some references done by the great mathematician Leonhard Euler with some special examples. Consequently, we have established a relation to estimate the sum of convergent infinite series